A clinico epidemiological study of cut throat patients – An observational retrospective study at tertiary care hospital in Jharkhand, India - Md. Noman Alam; Sandeep Kumar; Md. Anas (Asian Journal of Medical Sciences, 2023)
Background: Cut throat injury is an incised wound in the neck that may be superficial or deep and is usually caused by sharp objects. These wounds may be from homicide, suicide, or accidental. Aims and Objectives: The purpose of this study was to assess cut throat injury in terms of age, sex, site of injury, and triggering factors for suicidal cut throat injury. Materials and Methods: This retrospective study was carried out in the Department of ENT, Rajendra Institute of Medical Sciences. The study included 35 cut throat patients who were admitted and managed in the ENT department. Data were analyzed with detailed history as age, sex, cause, site of injury, sociodemographic pattern, and history of substance abuse, psychiatric problem, and duration of hospital stay. Results: Out of 35 patients, 32 were male and three were female. The majority of the patients 21 (60%) were young adults. Causes of cut throat were suicidal 77.14% followed by homicidal 20%. The majority of patients had Zone II injuries. In general, the patients belonged to the lower middle socioeconomic class. About 77.8% of patients with suicidal cases were found to be addicted to one more substance and 22.2% were having some psychiatric illness. The most common substance abuse was indigenous rice beer Hadia mahua. Conclusion: Young adults of the low socioeconomic class were most vulnerable to cut throat injury with a majority having zone II injury. Suicide was the most common cause with substance abuse proving to be a major provoking factor in addition to unemployment, illiteracy, and poverty.